Clinical and molecular spectrum along with genotype-phenotype correlation of 25 patients diagnosed with 3 M syndrome: a study from Turkey - Akalin, Akcahan; Ozalkak, Servan; Yildirim, Ruken; Karakaya, Amine Aktar; Kolbasi, Baris; Durmusalioglu, Enise Avci; Elcioglu, Nursel H. (Springer, 2024)
3 M syndrome is a well-known autosomal recessive skeletal genetic disorder caused by biallelic pathogenic variants in the CUL7, OBSL1, and CCDC8 genes. Affected individuals exhibit profound pre- and postnatal growth retardation, distinctive facial features with normal intelligence. This study aims to provide insight into the comprehensive evaluation of clinical, laboratory, and radiological findings, expand the mutational spectrum of the disease, and establish a genotype-phenotype correlation in the present cases. A total of 25 patients from 19 unrelated families were included in the study. Genetic etiology was determined in probands through the utilization of Sanger sequencing and/or targeted gene panel analysis. The clinical, laboratory, and genetic features of all patients at admission and during follow-up were documented. Genotype-phenotype correlation was carried out in the CUL7 and OBSL1 groups. The genetic etiology was established in all patients (n = 25/25, 100%). We identified 15 distinct variants in CUL7, OBSL1, and CCDC8 genes, with eleven being novel. CUL7 variants were present in 13 patients (n = 13/25, 52%), while OBSL1 variants were found in 11 patients (n = 11/25, 44%). No notable distinctions were found in mean birth weight, height, and standard deviation scores between the CUL7 and OBSL1 mutation groups (p > 0.05). Patients with CUL7 variants exhibited significantly lower height standard deviation scores both at admission and at the last examination, as well as lower weight standard deviation scores at the last examination, compared to those with OBSL1 variants (p < 0.05). Conclusion: To date, genotype-phenotype correlations have been identified in a limited number of studies. Further research involving larger cohorts is necessary to solidify these correlations.
Keywords: Short stature; Genotype-phenotype correlation; CUL7; OBSL1; CCDC8